Ultrasonic Velocity and Attenuation in Epoxy Resin/Granite (Marble) Powder Composite. Issue 1 (2nd January 2018) - Yassene, Ali A. M.; Fares, S.; Ashour, A.; Abd El-Rahman, M.
ABSTRACT: In this research, gamma radiation has been used to graft styrene and acrylic acid monomers onto marble (M) and granite (G) powder, with irradiation doses 30, 10 kGy, respectively. The grafted marble and granite powders were used as filler of epoxy composites. They added to an epoxy resin at 20, 60, and 100 wt% and then cured at room temperature. Ultrasonic velocities and attenuation measurements in epoxy composites at 4 MHz in the 25–300°C temperature range in addition to Fourier Transform Infrared (FTIR) analysis had been investigated. The ultrasonic compression wave velocity and the shear wave velocity measurements were performed using the pulse-echo technique, and then wecalculated elastic modulus, Young's modulus, longitudinal and shear moduli, and Poisson's ratio. In addition to attenuation at different temperatures of epoxy/granite composites, ultrasonic results indicated that the ultrasonic wave's velocities VL and Vs increased with the increase of (M, G) content and a linear relation was observed. Also, the attenuation of epoxy was stable and appeared to increase at temperature 385°C, while the addition M or G to epoxy composites increased the attenuation.